DAMPAK SOSIAL TERHADAP PERKEMBANGAN DAKWAH - Ali, Mukti; Budyastomo, Avin Wimar; Harun, Makmur Haji (IAIN Pekalongan, 2021)
This study aims to determine the impact of social media in developing da'wah in Indonesia. Social media that is often used by the Indonesian people can be trusted to bring about changes in the behavior and methods of preaching to be conveyed. Currently, scholars in developing their preaching have also used social media. This type of research is descriptive qualitative by describing the findings or data available in the field then described as information. The method used is a direct interview with respondents about the impact of social media on the development of da'wah in Indonesia. The results obtained are the impact of social media on the development of Da'wah is that currently Da'wah has used technology such as social media for the propagation of Da'wah. Most scholars preach using social media such as YouTube and Facebook. This makes it easier for the scholars to preach.